Bioefficacy of efficient entomopathogenic fungus against branch canker pathogen (Macrophoma theicola) in tea plantations of southern India - J MAREESWARAN; P NEPOLEAN; R JAYANTHI; R PREMKUMAR SAMUEL ASIR; B RADHAKRISHNAN (The Indian Journal of Agricultural Sciences, 2016)
Three branch canker pathogens, viz. NBCHE-6, UPA-61 and VPM were isolated from different tea growing districts of south India and four entomopathogenic fungus, viz. Beauveria bassiana, Paecilomyces lilacinus, Lecannicillium lecannii and Paecilomyces fumosoroseus were procured from the microbial type culture collection and gene bank (MTCC), Chandigarh. In vitro studies revealed that Beuveria bassiana showed highest antagonistic effect against NBCHE-6 (64.22) followed by Paecilomyces fumosoroseus against UPA-61(56.66). Paecilomyces lilacinus significantly controlled VPM (54.66), while Lecannicillium lecannii showed insignificantly control against VPM (47.33). While Beuveria bassiana and Paecilomyces lilacinus coiled around and shrink branch canker pathogen, Lecannicillium lecannii breaks into branch canker hyphae and Paecilomyces fumosoroseus produces more spore to kill branch canker. In culture filtrate studies, Paecilomyces fumosoroseus and Paecilomyces lilacinus showed maximum control of VPM (68.44) and UPA-61 (65.59). Beauveria bassiana also showed significant control of two isolates VPM and UPA-61 (54.44). Lecanniicillium lecannii showed least control of VPM (30.44). This study concludes that entomopathogens can significantly control branch canker pathogen (Macrophoma theicola).